Implementasi Model Team Game Tournament Berbasis Monopoli Interaktif untuk Meningkatkan Pemahaman Siswa SMP Tentang Mitigasi Bencana Atmosfer dan Polusi Udara - Lutfiyanti, Rosa Azzahro; Rahmawati, Dewi Syamsia; Az-zahro, Adhelia Carissa; Hendratmoko, Ahmad Fauzi; Sudibyo, Elok; Nurita, Tutut (STKIP HARAPAN BIMA, 2025)
Understanding atmospheric disaster mitigation is essential for students from an early age, especially since Indonesia is highly vulnerable to extreme weather events such as storms and heavy rainfall. Nevertheless, this topic is often perceived as less engaging and tends to lack student participation. This study investigates the effectiveness of the Teams Games Tournament (TGT) model integrated with Interactive Monopoly in enhancing students’ understanding of atmospheric disaster mitigation and air pollution. The research adopted a one-group pretest-posttest design involving 30 eighth-grade students. Data were analyzed using the N-Gain test to measure improvement in learning outcomes and the Wilcoxon test to determine the significance of differences between pretest and posttest scores. The findings revealed an increase in the average score from 78.83 (pretest) to 98.5 (posttest). The mean N-Gain score reached 0.94, which falls into the high category. The Wilcoxon test produced a significance value of 0.000 (p 0.05), confirming a significant difference. During the learning activities, students showed active involvement, effective collaboration, and greater motivation. The integration of TGT with Interactive Monopoly provides an innovative and enjoyable learning approach, statistically proven to improve learning outcomes, engagement, and motivation in contextual science education.